2022
DOI: 10.1149/1945-7111/ac9931
|View full text |Cite
|
Sign up to set email alerts
|

Composite Porous Structure Formation by Platinum-Particle-Assisted Etching of a Highly-Doped p-Type Silicon: Evaluation of Charge Flow in Silicon

Abstract: Electroless deposition of metal particles on silicon (Si) followed by the metal-assisted etching (metal-assisted chemical etching) is a simple way to fabricate Si nanostructures. A composite porous structure consisting of straight macropores and a mesoporous layer can be created by platinum (Pt)-particle-assisted etching. In this work, we studied the composite structure formation on a highly-doped p-Si (ca. 5×1018 cm−3) in comparison with a moderately-doped p-Si (ca. 1×1015 cm−3). The composite structure drast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 46 publications
0
13
0
Order By: Relevance
“…Previously, we studied the metal-assisted etching using Pt particles as the catalysts and measured the potential of Si during etching. 21,22,48 For example, the potentials of Pt-particle-deposited n-Si and p-Si were −0.25 V 48 and 0.07 V 21 vs Ag/AgCl, respectively. The potentials of Pt-filmdeposited n-Si (after the potential drop) and p-Si are similar to that of Pt-particle-deposited n-Si and p-Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we studied the metal-assisted etching using Pt particles as the catalysts and measured the potential of Si during etching. 21,22,48 For example, the potentials of Pt-particle-deposited n-Si and p-Si were −0.25 V 48 and 0.07 V 21 vs Ag/AgCl, respectively. The potentials of Pt-filmdeposited n-Si (after the potential drop) and p-Si are similar to that of Pt-particle-deposited n-Si and p-Si, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In platinum (Pt)-particle-assisted etching, a composite porous structure consisting of macropores and a mesoporous layer can be created. 11,[15][16][17][18][19][20][21][22] The macropores are formed by the dissolution of Si under the Pt particles, while the mesoporous layer is formed on the Si surface away from them. Recently, we demonstrated that the ratio of macropore depth and mesoporous layer thickness changes depending on the composition of etching solution 21 and doping density of Si.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4]7,8,10,[22][23][24][25][26][27][28][29][30][31][32] For example, when using platinum (Pt) catalysts, not only straight pores formed by the preferential dissolution of Si beneath the Pt catalysts but also mesopores covering on the entire surface of Si can be obtained. [33][34][35][36][37][38][39][40] However, the formation mechanism of the composite porous structure is not fully understood. We previously demonstrated that a characteristic composite structure (mesoporous layer thickness exceeds straight pore depth) is formed on highly-doped p-Si and the thick mesoporous layer can be attributed to the tunneling effect at the Si/electrolyte interface.…”
mentioning
confidence: 99%